Near-field enhancement in oxidized close gap aluminum dimers. (20th October 2020) - Simeone, Daniela; Tasco, Vittorianna; Esposito, Marco; Manoccio, Mariachiara; Lorenzo, Daniela; Scuderi, Mario; Luca, Antonio De; Cabrini, Stefano; Passaseo, Adriana; Cuscunà, Massimo
Abstract: Aluminum bowtie nanoantennas represent a possibility to confine and enhance electromagnetic (EM) field at optical frequencies in subwavelength regions by using an abundant and inexpensive metal. The native oxidation process of this metal is often viewed as a limitation for its application in plasmonics. Here, we show that in close gap configurations, the high refractive index of the native aluminum oxide helps in squeezing the plasmonic mode in extremely reduced size volumes, providing a higher EM near-field confinement and enhancement in the bowtie antenna gaps than achieved in the pure aluminum counterpart. Hence, the study provides new perspectives in the use of such a plasmonic antenna geometry within this aluminum system, which can be useful for improving plasmonics-enabled effects such as surface-enhanced Raman scattering- and light–matter interaction in strong coupling regime.